THE HYPOTENSIVE EFFECT OF CISAPRIDE IN RAT - YEGEN, BERRAK (ELSEVIER SCIENCE INC, 1994)
1. Cisapride is a prokinetic agent believed to facilitate acetylcholine release from the myenteric plexus of the gut. The aim of the present study was to investigate the effect of cisapride on blood pressure and the effects of muscarinic receptor antagonists on the cisapride-induced blood pressure changes. 2. Cisapride was given i.v. alone or 10 min after muscarinic receptor antagonists. Cisapride given i.v. produced a significant decrease in blood pressure in a dose-related manner. Atropine, AF-DX 116 and 4-DAMP given 10 min before cisapride injection, partially inhibited the hypotensive response to cisapride. In pithed rat, the effect of cisapride on blood pressure remained unaltered. 3. This study indicates that the action of cisapride is not through central mechanisms and part of cisapride's effect is through the cholinergic system.
Keywords: BLOOD PRESSURE; CISAPRIDE; CHOLINERGIC SYSTEM; INTRAVENOUS CISAPRIDE; MOTOR-ACTIVITY; GUINEA-PIG; GASTROPARESIS; CONTRACTION; STIMULATION